Pertumbuhan dan Perkembangan Ilmu Komunikasi - Haykal, Muhammad; Zuhra, Nabila; Effendi, Erwan; Sari, Winda; Nafidza, Selfa; Najmullah, Anwar (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The aim of this study is to learn how the ancient growth and development of the communication sciences made such a widespread development in the present era. The study employed a library study method by conducting a qualitative study method using a descriptive method. The study gathered data available from journals and books associated with the growth and development of communication sciences. The technique employed in this data collection involves recording and summarizing a number of obvious data sources. Analysis in this data collection suggests that the growth and development of communication sciences go through many processes in the stages of its development. The results of this study suggest that the growth and development of the communications science are constantly changing over the years and is thus growing rapidly and broadly in the present era.